2004
DOI: 10.1071/wr03031
|View full text |Cite
|
Sign up to set email alerts
|

Improving trapping success for rare species by targeting habitat types using remotely sensed data: a case study of the heath mouse (Pseudomys shortridgei) in Western Australia

Abstract: The rare heath mouse (Pseudomys shortridgei) is the only rodent lacking a conservation program in Western Australia. Little is known about the habitat requirements of P. shortridgei in Western Australia, and there is a lack of trapping focus that could target specific habitat components that this species may use. The purpose of this study was to (1) relate the occurrence of this species to measurable components of its habitat; (2) incorporate habitat information into a GIS modelling system to identify other ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Heath‐mouse relative abundance was not directly correlated with post‐fire age class. Previous studies have revealed contrasting associations between heath mice and age class, with results reflecting variable responses of heath mice to age class in the eastern population, and a preference for older age classes in the western population (Cockburn, 1978; Cooper et al ., 2003; Quinlan et al ., 2004; Salinas et al ., 2009; Di Stefano et al ., 2011). The spatially and temporally variable relationship between heath mice and fire is consistent with findings for other species (Nimmo et al ., 2014), likely reflecting interactions between fire and other processes (Hale et al ., 2016), and the fact that fire history variables only partially reflect changes in important resources (Swan et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heath‐mouse relative abundance was not directly correlated with post‐fire age class. Previous studies have revealed contrasting associations between heath mice and age class, with results reflecting variable responses of heath mice to age class in the eastern population, and a preference for older age classes in the western population (Cockburn, 1978; Cooper et al ., 2003; Quinlan et al ., 2004; Salinas et al ., 2009; Di Stefano et al ., 2011). The spatially and temporally variable relationship between heath mice and fire is consistent with findings for other species (Nimmo et al ., 2014), likely reflecting interactions between fire and other processes (Hale et al ., 2016), and the fact that fire history variables only partially reflect changes in important resources (Swan et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, subsequent studies of the eastern population have revealed variable fire responses, including no response to fire and interactions between fire and drought (Cooper et al ., 2003; Salinas et al ., 2009; Di Stefano et al ., 2011; Hale et al ., 2016). In contrast, the western population has shown a preference for older successional vegetation (Quinlan, Moro & Lund, 2004). Despite an absence of a successional preference in the eastern population, heath mice responded to aspects of vegetation structure, indicating that fire history may be a poor proxy for their abundance (Di Stefano et al ., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Early studies (Cockburn 1978;Cockburn et al 1981) showed that floristic diversity and early stages of habitat succession following fire were important features for determining the presence and abundance of P. shortridgei. More recently, the species has been found in habitats that have not been burned for many years, thus throwing some doubt on earlier predictions that fire history is an important predictor of distribution (Cooper et al 2003; Department of Sustainability and Environment (DSE) 2003; Quinlan et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The rediscovery of P. shortridgei in Western Australia is an interesting story of coincidence, including re-identification of museum specimens labelled as the Bush Rat (Rattus fuscipes), bones in fresh owl pellets and trapping live P. shortridgei, all within a month of each other! Recent records of P. shortridgei are known from limited locations in western Victoria (Menkhorst 1995) and Western Australia (Cooper et al 2003;Quinlan et al 2004), in woodland with an understorey of heathy shrub species, low forest, and dry and wet heath. Soil types include sands, loams and gravels derived from laterite, calcarenite, limestone and sandstone.…”
Section: Introductionmentioning
confidence: 99%